The contribution of ports to shipping decarbonization: An analysis of port incentive programmes and the executive role of port state control - Peyman Ghaforian Masodzadeh; Aykut I. Ölçer; Fabio Ballini; Dimitrios Dalaklis (Transport Economics and Management)
In policy design, the contribution of ports to shipping decarbonization has been underestimated. Port incentive programmes have not contributed significantly to shipping decarbonization, and in the implementation of energy regulations, the role of the port state control has been exclusively limited to document control. This study aims to analyse the role of ports in shipping decarbonization by conducting an online survey and interviewing experts. We examine two proposals: first, a global incentive scheme focused solely on CO2 reduction, supported by the GHG Fund of the future IMO carbon pricing mechanism, acting as a rebate mechanism, and second, a voyage-based data collection and verification system. Experts have strongly supported the first proposal. The second proposal is technically feasible, since some verification firms and pioneer shipping companies have already started this practice. It is economically also feasible at a minor cost. A differentiated bunker levy based on these proposals is recommended at the end, in which ports play a significant role.